Optimasi Formula Tablet Floating Nifedipin Menggunakan HPMC K15M, PVP K-30 dan Avicel PH 102 dengan Metode Simplex Lattice Design - Aisiyah, Siti; Fudholi, Achmad; Rohman, Abdul (Jurnal Farmasi (Journal of Pharmacy), 2013)
Nifedipine is a drug with a small solubility in water, a consequence, in order to obtain the desired drug release, the solubility of nifedipine should be increased by the addition of PVPK-30.This study was aimed to know the effect of HPMC K15M, PVP K-30 on the release of nifedipin, and Avicel PH 102 on the floating lag time of nifedipine floating tablet, and to find out the proportion of each ingredient to produce the optimum formula of nifedipin floating tablet. The study was conducted using Simplex Lattice Design (SLD) with 3 components i.e. HPMC K15M, PVPK-30 andAvicel PH 102 in order to obtain 14 formulas. The optimization parameter consists of absorption tablet, floating lagtime, C360 and DE360. The four parameters were analyzed using Design Expert7.1.3 software to determine the optimum formula. The optimum formula was obtained by determining the desired target for each parameter. The absorption was selected in maximum target, floating lag time was selected in minimum target, C360 targeted at number 54 and DE360 targeted at number 40. HPMC K15M at the highest concentration affected the smallest release of nifedipin, the highest PVP K-30 concentration affected the most of nifedipin release, where as high concentration Avicel PH 102 had a small affected reduce in floating lag time of nifedipin floating tablet. The composition of the optimum formula is as follows: 80mg HPMC K15M, 97mg PVPK-30 and 45mg Avicel PH 102. The results of tablet absorption, C360 and DE360 did not differ significantly; floating lag time gave significantly different results to obtain from software. The release kinetics of all formulas fit order 1, which indicated that the drug release occurred through a diffusion mechanism.